Case Series of Disseminated Xanthogranulomatosis in Red-crowned Parakeets (Cyanoramphus novaezelandiae) with Detection of Psittacine Adenovirus 2 (PsAdV-2) - Cornelia Konicek; Kristin Heenemann; Kerstin Cramer; Thomas W. Vahlenkamp; Volker Schmidt (Animals, 2022)
Xanthogranulomatosis is a common dermatological disease in birds. This form of inflammation, possibly associated with lipometabolic disorders, can also be seen in visceral organs, which as yet has only rarely been described in avian medicine. In general, diseases related to impaired lipid metabolism are frequently reported in avian medicine, with hepatic steatosis and atherosclerosis being the most common. In human medicine, infectious agents—especially some strains of adenovirus—were implicated in contributing to lipometabolic disorders; this has also been described for chicken. Here, a case series of six Red-crowned Parakeets (Cyanoramphus novaezelandiae) is presented, all cases being characterized by psittacine adenovirus 2 (PsAdV-2) infection with or without disseminated xanthogranulomatosis. The affected individuals were examined alive by clinical examination. Total body radiographs were taken of two birds, haematology and blood biochemistry results were achieved in one bird. The birds either died immediately after clinical presentation or within two days, two individuals were euthanized due to worsening of their clinical condition. All birds underwent a post-mortem examination. While four birds were finally diagnosed with disseminated xanthogranulomatosis, all six individuals had large eosinophilic intranuclear inclusion bodies in the epithelial cells of the collecting ducts of the kidney and tested positive for PsAdV-2. Further examinations are needed to clarify to what extent PsAdV-2 might elicit lipometabolic disease in birds, or psittacines in general, and, in particular, the Red-crowned Parakeet.